The Chinese Association for the Study of Pain (CASP): Expert Consensus on the Cervicogenic Headache - Hong Xiao; Baogan Peng; Ke Ma; Dong Huang; Xianguo Liu; Yan Lu; Qing Liu; Lijuan Lu; Jingfeng Liu; Yimei Li; Tao Song; Wei Tao; et al. (Pain Research and Management)
Cervicogenic headache is a relatively common but unique form of headache, and in China, as well as in several other countries, both diagnosis and a clear evidence-based treatment plan remain controversial. Therefore, the Chinese Association for the Study of Pain organized a meeting of pain management experts and created an expert consensus on the diagnosis and treatment of cervicogenic headache in China. This article summarizes the conclusions of the consensus group regarding the epidemiology, etiology, clinical features, diagnosis, differential diagnosis, treatment, and rehabilitation of cervicogenic headache in China.